Performance of forest plantations in small and medium-sized farms in the Atlantic lowlands of Costa Rica - Piotto, D.; Montagnini, F.; Ugalde, L.; Kanninen, M. (2003)
Exotic tree species predominate in reforestation in tropical regions worldwide. However, some native species are suitable for plantations, providing a wider variety of products. Adequate government programs of incentives, coupled with good technical advice to farmers, are needed to stimulate reforestation, especially among small and medium-sized farmers with limited financial resources. This project evaluates growth of native and exotic tree species on plantations in small and medium-sized farms in the Atlantic humid lowlands of Costa Rica, Central America. A total of 210 pure plantations, ranging in age from 6 to 11 years, were evaluated on 123 farms that had used government incentives for reforestation, and had received technical advice from local non-government organizations. For each species, seven plantations were chosen at random for study. In each plantation, plots of 15 trees each were chosen systematically for evaluation of diameter at breast height (dbh), total height, number of trees per hectare, tree form and spacing. Terminalia amazonia (J.F. Gmel) Exell, Hieronyma alchorneoides Allemao, and Vochysia guatemalensis Donn. Sm. were the most frequent species found in plantations in the region of study. Gmelina arborea Roxb. (exotic) and V. guatemalensis (native) had the highest mean annual diameter increment with 2.90 and 2.59 cm, respectively. Calophyllum brasiliense Cambess. (native) had the lowest mean annual diameter increment (1.48 cm). G. arborea and V. guatemalensis had the highest mean annual volume increment, followed by Tectona grandis (L.f) Lam. (exotic), and T. amazonia and Cordia alliodora (R&P) Cham. (both native). Although G. arborea had the greatest mean annual diameter increment, it had the lowest plantation density and problems with form. V. guatemalensis and T. amazonia, two native species, were the most promising species for reforestation, due to good growth in volume, good form, and adaptability to a variety of sites. The poor form of exotic species was related to the low intensity management methods of small farmers. Exotic species had the highest performance variability between sites, while native species showed relatively high growth homogeneity. Therefore, native species seem more promising than exotics for general use across varying ecological conditions.